Tantalum based amorphous thin films as copper diffusion barrier - Yan, Hua (2013)
This dissertation presents a study of Ta-based Cu diffusion barrier for advanced semiconductor technology. With the fast development of semiconductor industry, a novel barrier is required in order to address two challenges in the back-end-of-line technology: enhancing the interconnect reliability of back-end-of-line and reducing resistance-capacitance delay faced during further scaling of semiconductor devices.